1979
DOI: 10.1042/bj1800545
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine aminotransferase induction in hepatocytes cultured from rat foetuses treated with dexamethasone in utero

Abstract: 1. The administration of dexamethasone to foetal rats in utero does not result in the appearance of specific tyrosine aminotransferase activity even after 24h. 2. When foetal hepatocytes are cultured in vitro from animals treated in utero with dexamethasone, significantly higher activities of specific tyrosine aminotransferase are found than in untreated controls. 3. Dexamethasone in vitro induces specific tyrosine aminotransferase in cells cultured from control animals, and the effect is maximal at 10nM in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…mASAT, mitochondria1 aspartate aminotransferase. coids (37). In the case of our patients, the situation is similar to that in fetal and premature neonatal liver.…”
supporting
confidence: 61%
“…mASAT, mitochondria1 aspartate aminotransferase. coids (37). In the case of our patients, the situation is similar to that in fetal and premature neonatal liver.…”
supporting
confidence: 61%
“…The enzymatic differentiation of developing rat liver has proved to be a useful model for these studies. During development, most rat liver enzymes accumulate rapidly and in discrete groups or clusters: the late fetal cluster (16)(17)(18)(19)(20)(21)(22) days ofgestation), the neonatal cluster, and the late suckling cluster (1).…”
mentioning
confidence: 99%
“…This assumption was supported by results of previous work which demonstrated that premature delivery of fetuses of rats and other experimental animal species, or administration of either glucagon or dibutyryl-CAMP to rat fetuses in utero resulted in the precocious appearance of the enzyme in the liver (Litwack and Nemeth, 1965;Greengard and Dewey, 1967;Holt and Oliver, 1968;Greengard, 1969). Similarly, TAT activity has also been observed both in fetal liver explants ( Ruiz-Bravo and Ernest, 1982) and in monolayer cultures (Yeoh et al, 1979a(Yeoh et al, , 1979b. Together, the results were interpreted to mean that the environment in utero might be responsible for suppressing the synthesis of TAT in the fetal liver (Cake et al, 1989).…”
Section: Discussionmentioning
confidence: 88%